MiR-503 enhances the radiosensitivity of laryngeal carcinoma cells via the inhibition of WEE1 - Huimin Ma; Rong Lian; Zhiyan Wu; Xiao Li; Wenfa Yu; Yun Shang; Xixia Guo (Tumor Biology)
Enhancing the sensitivity of laryngeal cells to radiation is crucial for improving the efficacy of laryngeal carcinoma. MicroRNAs are known to play a major role in regulating cellular radiosensitivity. This study was designed to explore the effect and the molecular basis of miR-503 in the radiosensitivity of laryngeal carcinoma cells. Quantitative real-time polymerase chain reaction analysis showed that miR-503 expression was decreased in human laryngeal carcinoma cell lines Hep-2 and TU212, and the downregulation of miR-503 was also observed after irradiation. Upregulation of miR-503 by pre-miR-503 transfection restrained proliferation, promoted progression of Hep-2 and TU212 cells through the cell cycle after irradiation, and sensitized cells to radiation. Dual-Luciferase Reporter Assay verified a direct interaction between miR-503 and the WEE1 messenger RNA 3’-untranslated region. The overexpression of miR-503 significantly decreased WEE1 expression at the messenger RNA and protein levels, whereas the inhibition of miR-503 upregulated the expression of WEE1. WEE1 knockdown by WEE1 small interfering RNA apparently abrogated the inhibitory effect of anti-miR-503 on radiosensitivity. In conclusion, miR-503 could function as an enhancer of radiation responses in laryngeal carcinoma cells by inhibiting WEE1, which may be a potential novel radiosensitizing strategy for laryngeal carcinoma.